2010
DOI: 10.1016/j.neuroscience.2010.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Temporally- and spatially-regulated transcriptional activity of the nicotinic acetylcholine receptor β4 subunit gene promoter

Abstract: Signaling through nicotinic acetylcholine (nACh) receptors underlies a diverse array of behaviors. In order for appropriate signaling to occur via nACh receptors, it is necessary for the genes encoding the receptor subunits to be expressed in a highly regulated temporal and spatial manner. Here we report a transgenic mouse approach to characterize the transcriptional regulation of the gene encoding the nACh receptor β4 subunit. nACh receptors containing this subunit play critical roles in both the central and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 76 publications
1
15
0
Order By: Relevance
“…Two regulatory elements have also been found that direct the expression of the clustered nAChR genes in a tissue-specific manner: β43´, found at the β4 3´-untranslated region, and CNR4, a conserved noncoding region located 20 kb upstream of β4 (Xu et al 2006). Recently, we showed that a 2.3-kb fragment of the β4 gene promoter directs spatially and developmentally regulated expression of a reporter gene in vivo (Bruschweiler-Li et al 2010). Whether this region also regulates expression of the α3 and α5 genes remains to be determined.…”
Section: The α3/α5/β4 Nachr Subunit Gene Clustermentioning
confidence: 99%
“…Two regulatory elements have also been found that direct the expression of the clustered nAChR genes in a tissue-specific manner: β43´, found at the β4 3´-untranslated region, and CNR4, a conserved noncoding region located 20 kb upstream of β4 (Xu et al 2006). Recently, we showed that a 2.3-kb fragment of the β4 gene promoter directs spatially and developmentally regulated expression of a reporter gene in vivo (Bruschweiler-Li et al 2010). Whether this region also regulates expression of the α3 and α5 genes remains to be determined.…”
Section: The α3/α5/β4 Nachr Subunit Gene Clustermentioning
confidence: 99%
“…44 Further, rs3813567 is located within the CHRNB4 promoter, which contains key regulatory elements, and is important to the temporal and tissue specific regulation of CHRNB4. 45,46 Regulation of the 15q24 region is complex with CHRNA5, CHRNA3 and CHRNB4 often being co-expressed. CHRNB4 contains a 3′ enhancer element involved in this combined regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The 2,346-base pair SacI/HindIII fragment of the rat β4 subunit gene was excised from the pSGB4SH construct (Bruschweiler-Li et al, 2010) and used as the template for mutagenic polymerase chain reaction (PCR). For mutagenesis, the primers were designed to make 3 base substitutions in the CA box within the context of the 2.3-kb promoter fragment (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This regulatory element, deemed the CA box due to its nucleotide composition, is also the binding site for several transcription factors in vivo (Scofield et al, 2008). We recently demonstrated that a 2.3-kb fragment of the β4 promoter region containing the CA box is capable of directing cell-type specific and developmentally regulated expression of a reporter gene in vivo (Bruschweiler-Li et al, 2010). …”
mentioning
confidence: 99%